Effects of entomopathogenic fungi on natural enemies: a systematic review of their use in biological control - Albana, Hasan; Nur Ain Izzati Mohd Zainudin,; Noraini Abu Bakar,; Saputra, Nanda; Dashika Devi Mailvaganam,; Wan Mohd Syazwan,; Syahrawati, My (Penerbit Universiti Kebangsaan Malaysia, 2025)
This review evaluates the potential negative impacts of entomopathogenic fungi (EPF) on natural enemies, a key component of sustainable pest management. Literature from Scopus and PubMed, covering 12 countries, 13 EPF species, and 33 natural enemy species, was classified according to the International Organization for Biological Control (IOBC) scale. EPF often caused lethal effects, such as Lecanicillium muscarium killing the parasitoid Diaeretiella rapae, as well as sublethal effects, including reduced reproduction, shortened longevity, decreased survival rates, and prolonged development. These outcomes varied depending on specific EPF–natural enemy interactions. The findings highlight the need for more field-based and long-term studies to ensure EPF applications do not compromise the ecological role of natural enemies in Integrated Pest Management (IPM).